The Usefulness of Antigen Testing in Predicting Contagiousness in COVID-19 (2022)
ABSTRACT: Increasing the diagnostic capacity for COVID-19 (SARS-CoV-2 infection) is required to improve case detection, reduce COVID-19 expansion, and boost the world economy. Rapid antigen detection tests are less expensive and easier to implement, but their diagnostic performance has been questioned compared to reverse transcription-PCR (RT-PCR). Here, we evaluate the performance of the Standard Q COVID-19 antigen test for diagnosing SARS-CoV-2 infection and predicting contagiousness compared to RT-PCR and viral culture, respectively. The antigen test was 100.0% specific but only 40.9% sensitive for diagnosing infection compared to RT-PCR. Interestingly, SARS-CoV-2 contagiousness is highly unlikely with a negative antigen test since it exhibited a negative predictive value of 99.9% compared to viral culture. Furthermore, a cycle threshold (CT) value of 18.1 in RT-PCR was shown to be the one that best predicts contagiousness (area under the curve [AUC], 97.6%). Thus, screening people with antigen testing is a good approach to prevent SARS-CoV-2 contagion and allow returning to daily activities.